2021
DOI: 10.1101/2021.01.27.428438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural diversity of honey bee (Apis mellifera) gut bacteriome in various climatic and seasonal states

Abstract: As pollinators and producers of numerous human consumed products, honey bees have great ecological, economic and health importance. The composition of their bacteriota, for which the available knowledge is limited, is essential for their body's functioning. Based on our survey we performed a metagenomic analysis of samples collected by repeated sampling from representative geolocations regarding the study area's climatic types over two nutritionally extreme periods (March and May) of the collection season. In … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 98 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…In another study examining the composition of the intestinal bacteriota of honey bees, a significant difference was found between the samples taken in March and May. A significant difference in composition was reported between the colder and warmer regions in the intestinal contents of the March samples (Papp et al, 2021). In another study, it was determined that the diversity of the general gut microbiota varied significantly according to the type of diet (Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…In another study examining the composition of the intestinal bacteriota of honey bees, a significant difference was found between the samples taken in March and May. A significant difference in composition was reported between the colder and warmer regions in the intestinal contents of the March samples (Papp et al, 2021). In another study, it was determined that the diversity of the general gut microbiota varied significantly according to the type of diet (Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Bartonella is a commensal bacterium in honey bees with high prevalence yet low abundance. However, sporadic elevation of Bartonella in summer has also been reported occasionally ( 52 , 64 ). Possible reasons may include altered diet, temperature change, and behavioral variation of the workers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increasing studies have pointed to its correlation to cold conditions. For example, Papp et al ( 52 ) revealed temporal shifts in Bartonella with increased abundance were only found at cooler sites. In particular, more studies have shown that Bartonella significantly increased during winter ( 36 , 51 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation